Uwarunkowania poczucia dobrostanu psychicznego u dzieci w środowisku szkolnym - Marzanna Farnicka; Hanna Liberska (Problemy Wczesnej Edukacji)
The paper presents the results of a study aimed at the identification of selected subjective and situational determinants of the well-being of children and their adaptation to the environment of an elementary school. The study was conducted on a group of pupils from grades II to V (N = 173) and was based on an analysis of the questionnaires: SPAS (Boersma Chapman 1979), SUSPO (Mikšik 2004) and own tool QSL. The results indicated the determinants of changes in well-being in time related to the sense of exclusion and level of sadness. An analysis of the data pointed to the spheres of the educational environment changes in which could increase the level of child satisfaction from schooling and learning.